Digital marketing: analysis of current trends in Ukraine and worldwide. - Sak, Tetiana V.; Chulipa, Ihor D. (My University, 2024)
The article provides a comprehensive overview of contemporary trends in digital marketing. It examines general trends in digital marketing, encompassing both global practices and the specifics of the Ukrainian market. Special attention is given to social media marketing, where new platforms and innovative audience engagement methods are analyzed, and the latest SMM trends are identified. A significant amount of the research addresses the international development of influencer marketing, highlighting key success factors and the main challenges brands encounter when working with influencers. The study also analyzes and discusses current trends in email marketing, including innovative approaches to automation and personalization of communications, which enhance campaign effectiveness. The article emphasizes the future prospects of digital marketing, particularly on emerging technologies such as artificial intelligence and big data analytics. It is established that successful implementation of marketing strategies requires constant adaptation to changing market conditions and technological advancements in digitalization.
Keywords: цифровий маркетинг; цифрові інструменти; 339.138:004